THE ACOUSTIC QUALITY OF SEKOLAH ALAM CLASSROOM (CASE: SEKOLAH ALAM IN BANDUNG) - widyarko widyarko (International Journal on Livable Space, 2020)
ABSTRACT Sekolah Alam (The Nature School) is a new concept of school in Indonesia that divide its learning process, both indoor and outdoor. As it needs more outdoor space for learning activity, this type of school has larger yards yet smaller classroom compared to conventional school. As it is still new, no previous study has been done to understand the relation between space dimensions, building material, and surroundings to this school classroom acoustic quality. Therefore, this journal studied acoustic quality by calculating Reverberation Time (RT60) and measuring Background noise value of one typical class of Sekolah Alam in Bandung. Reverberation Time (RT60) was calculated using space dimensions and materials that exist within the studied classroom, while the background noise value was measured using Data Logging Sound Level Meter (SLM). The results indicate that the studied class has an ideal acoustic quality for learning activity. The main factors that affected these results are the classroom has a small size in volume and surrounded by lush trees which work as noise controls. Keywords: Reverberation Time; Background Noise; Sekolah Alam; Nature School; Classroom; Elementary School